Konsep Pendidikan Jiwa Menurut Ibn. Al-Qayyim Al-Jauziyyah - Sudarto Sudarto (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2021)
Islamic education continues to roll with various kinds of development according to its era from period to period, from time to time. History shows that the development of educational activities during the classical period of Islam has brought Islam as a bridge for scientific development from classical science to modern scholarship. However, subsequent generations of Muslims did not inherit the scientific spirit of their predecessors. As a result, the achievements that have been made have changed hands to the West. The research method in this paper is related to the thoughts of Ibn al-Qoyyim al-Jauziyyah. Then the method that will be used to express his thoughts is a qualitative method. The data collected by collecting written sources in the form of documents in the form of books and other documents. Such a dirty soul is classified into three groups, namely: a soul that orders evil, a soul that repents, a soul that makes it easy to make mistakes. The essence of cleansing the soul is to realize monotheism in one's life, this is the secret of Allah Subhanahu wa Ta'ala when sending the prophets of the Prophet all carrying the same mission, namely the preaching of tauhid. The concept of Ibn al-Qoyyim al-Jauziyyah's mental education is divided into two dimensions; first, the dirty soul and second, is the way to cleanse the soul. The essence of this mental madrasa is Tahqiiqul 'Ubudiyyah (Iyyaaka Na'budu wa Iyyaaka Nasta'iin)